Kinetic Study of Decomposition of Aqueous Hydrogen Peroxide by Colloidal Manganese Dioxide - Satapathy, P.K.; Rana, S.K.; Das, N.N. (Asian Journal of Chemistry, 2010)
The kinetics of the decomposition of aqueous hydrogen peroxide by water-soluble colloidal manganese dioxide (obtained by reduction of potassium permanganate with sodium thiosulphate) has been studied in the absence and presence of aqueous perchloric acid solution. The reaction followed pseudo first order kinetics with respect to [MnO2], fractional order with respect to [HClO4] and first order kinetics with respect to [H2O2].